Analysis a DU Pont In Assessing Performance Post-Merger Bsi Finances (2021-2022) - Faizah, Iva; Apriyani, Dian; Rahmawati, Nadila; Aulia, Verissa Regita (Al-Mashrof: Islamic Banking and Finance, 2024)
The aim of this research is to determine the financial performance of Bank Syariah Indonesia. After the merger for the 2021-2022 period using the du pont system method. The data used is secondary data in the form of financial report data from Bank Syariah Indonesia, Quarter I-III in 2021 and financial report data from Bank Syariah Indonesia Quarters I-III 2022, as well as journals and theses related to this research. From the data analysis carried out on the financial reports of the last two years using the financial performance method carried out by Bank Syariah Indonesia in 2021-2022 using the Du Pont System method, it has fluctuated or changed. This can be seen from the Du Pont table which shows the condition of the ratios which change in each period. The Net Profit Margin and Equity Multiplier ratios show an increase in the ratio in each period, while the Return on Investment and Return on Equity ratios increase in each period, but these ratios experience a decrease when entering the first quarter period in 2022.